SAVE ME THE WALTZ AND ZELDA FITZGERALD’S “VISUAL MUSIC”: AN INTERVIEW WITH ERIN P. TEMPLETON - Lanius, Marcela (Organon, 2019)
Erin E. Templeton is a Professor of English and Dean of the School of Humanities, Sciences, and Business at Converse College. She wrote the introduction to the 2019 Handheld Press edition of Zelda Fitzgerald’s novel Save Me the Waltz and contributed to a cluster of essays titled “Reading The Waste Land with the #MeToo Generation” in Modernism/modernity’s PrintPlus platform. She has also published essays on William Carlos Williams’s long poem Paterson for the Cambridge Companion to William Carlos Williams and contributed several entries to The Routledge Encyclopedia of Modernism on figures such as F. Scott Fitzgerald, Zelda Fitzgerald, T. S. Eliot, and Ezra Pound. Following the 15th International F. Scott Fitzgerald Society Conference that took place at the University of Toulouse-Jean Jaurès in June 2019, Professor Templeton agreed to discuss Zelda Fitzgerald’s Save Me the Waltz, her preface to the 2019 Handheld Press edition of the novel, and how the #MeToo movement has prompted new readings of well-established literary works.